Relationship of Microalbuminuria Levels among Patients with Type 2 Diabetes and its Complications in Western Uttar Pradesh - Abhishek; Shivangi Gupta; Anil Kumar Kem (Asian Journal of Medical Research, 2019)
Background: To study the relation of levels of microalbuminuria among patients with type 2 diabetes and its complication in western UP.Subjects and Methods:The study included 110 patients with Type 2 diabetes mellitus visiting the diabetic clinic. Patients with complications, such as retinopathy and neuropathy were diagnosed on the basis of history, clinical examination and investigations. Microalbuminuria levels were compared in patients with complications (subjects) of Type 2 diabetes mellitus and patients without complications (control). Results:The study revealed that microalbumin levels in the urine are at significantly higher range in patients with complications (p<0.05) mainly with diabetic retinopathy, as compared to patients with other complications. Conclusion: The study supports that microalbuminuria is significant among patients with diabetic complications and strict glycemic control can prevent microalbuminuria and thereby prevent progress on to diabetic nephropathy in patients with Type 2 diabetes mellitus.